Voters elect politicians who closely matched their preferences - Marco Portmann; David Stadelmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2012)
What determines political candidates' election prospects' We match roll call votes of candidates for the majority elected upper house of parliament who were previously in the lower house with revealed preferences of their constituency. Thereby, we obtain a direct measure of past congruence. Politicians have a significantly and quantitatively important higher probability of election when they more closely matched the preferences of their constituency. This pr ovides evidence for the direct retrospective voting rule that voters elect politicians who represented their preferences well.
Keywords: D72; D70; 330; Retrospective Voting; Voting Behavior; Representation; Constituents' Preferences